CNSC-02. BREAST TO BRAIN METASTASIS IS EXACERBATED WITH CHEMOTHERAPY THROUGH BLOOD-CEREBRAL SPINAL FLUID-BARRIER AND INDUCES ALZHEIMER'S-LIKE PATHOLOGY. (14th November 2022) - Neman, Josh; Saatian, Behnaz; Deshpande, Krutika; Martisorian, Vahan; LaViolette, Peter; Boire, Adrienne; Chow, Frances; Hurth, Kyle; Fecci, Peter; Shiroishi, Mark; Eisenbarth, Rachel
Abstract: Control of breast to brain metastasis remains an urgent unmet clinical need. While chemotherapies are essential in reducing systemic tumor burden, they have also shown to promote non-brain metastatic invasiveness and drug-driven neurocognitive deficits through formation of neurofibrillary tangles (NFT) independently. Now, in this study we investigated the effect of chemotherapy on brain metastatic progression and promoting tumor-mediated NFT. Results show chemotherapies promote increased brain-barrier permeability and facilitate enhanced tumor infiltration, particularly through the blood-cerebrospinal fluid-barrier (BCSFB). This is attributed to increased expression of matrix metalloproteinase 9 (MMP9) which, in turn, mediates loss of Claudin-6 within the choroid plexus cells of the BCSFB. Importantly, increased MMP9 activity in the choroid epithelium following chemotherapy results in cleavage of Tau released from breast cancer cells. This cleaved Tau forms tumor-derived NFT that further destabilize the BCSFB. Our results underline for the first time the importance of the BCSFB as a vulnerable point of entry for brain-seeking tumor cells post-chemotherapy and indicate that tumor cells themselves contribute to Alzheimer's-like tauopathy.